Tissue repair brakes: A common paradigm in the biology of regeneration. (28th November 2019) - Cigliola, Valentina; Ghila, Luiza; Chera, Simona; Herrera, Pedro L.
Abstract: To date, most attention on tissue regeneration has focused on the exploration of positive cues promoting or allowing the engagement of natural cellular restoration upon injury. In contrast, the signals fostering cell identity maintenance in the vertebrate body have been poorly investigated; yet they are crucial, for their counteraction could become a powerful method to induce and modulate regeneration. Here we review the mechanisms inhibiting pro-regenerative spontaneous adaptive cell responses in different model organisms and organs. The pharmacological or genetic/epigenetic modulation of such regenerative brakes could release a dormant but innate adaptive competence of certain cell types and therefore boost tissue regeneration in different situations. : Abstract : Cell identity maintenance, at all stages of life, is modulated by inhibitory signals from the surrounding cellular environment. Stress-mediated suppression of these signals, such as after a lesion, may lead fully mature differentiated specialized cells to change their function, thus fostering regeneration of injured tissue. Controlling this cellular plasticity could prove crucial to developing new therapies to treat degenerative diseases.